Autocontrol y comportamiento: efectividad de las técnicas autoinstruccionales en el aprendizaje de las operaciones aritméticas - Comas Mongay, M. D. (Enseñanza de las Ciencias. Revista de investigación y experiencias didácticas, 2006)
This experiment was designed to research the efficacy of self -instructional variables to improve performance in solving easy arithmetic problems. Children, boys and girls, six and seven years old, studying first school year of E.G.B., were used. The results, as a whole, tell us that training in self -instructional techniques significantly affects the dependent variable, decreasing the number of mistakes pupils make in arithmetical operations. It is appropriate to underline the group verbalizing the addition, which got the most significant reduction. These results, which confirm the findings of other authors, show the possibility of applying Cognitive-conductual techniques in the school frame.